Analysis of Sediment Samples and Erosion Potential: A Case Study of Upper Tamakoshi Hydroelectric Project - Koirala, Ravi; Chitrakar, Sailesh; Regmi, Surya Nath; Khadka, Manisha; Neopane, Hari Prasad; Thapa, Bhola (Hydro Nepal: Journal of Water, Energy and Environment, 2015)
Hydropower can be an effective green solution for meeting the current energy demand in Nepal. However, despite having tremendous water resources, only 2% of Nepal’s hydroelectricity potential has been tapped. Of the challenges that Nepali hydro faces, sediment erosion is a major one. Sediment erosion refers to an erosive tendency of sediment particles flowing with water over the exposed turbine parts including the runner. This paper deals with a sample analysis of sediment particles from the Upper Tamakoshi Hydroelectric Project. In this paper, we test for particle size distribution, particle count, mineral composition, and erosion potential analysis. For the mineral and erosion potential analysis, the sand samples range from 75 ìm to 200 ìm because the Tamakoshi plant consists of sediment traping system for particles larger than 150 ìm. The sediment samples were collected from three different points in the headrace and the severity of the effect of erosion has been analyzed in terms of depending variables like particle size, concentration, and mineral composition. DOI: http://dx.doi.org/10.3126/hn.v16i0.12216 HYDRO Nepal Journal of Water Energy and Environment Issue. 16, 2015, January Page: 28-31 Upload date: March 1, 2015